Depression among keratoconus patients: a systematic review and meta-analysis - Moshfeghinia, Reza; Arman, Ali; Sobhi, Navid; Mahmoudinezhad, Golnoush; Molavi Vardanjani, Hossein (Frontiers in Public Health, 2024)
Background: Keratoconus (KC) is a chronic corneal disease that typically presents in early adulthood, and may potentially result in poor mental health in affected individuals. The evidence regarding the association of depression with KC is controversial. Hence, we investigated the association between depression and KC via a systematic review and meta-analysis.Methods: Five electronic medical databases (PubMed, Scopus, PsycINFO, Web of Science, and CINAHL Complete) were systematically queried for English-language records from their inception to January 8, 2024. We include observational studies that measured the risk of depression or compared depression scores in KC patients in comparison to healthy ones. The Newcastle-Ottawa Quality Assessment Scale was utilized to assess bias risk in the included studies. Random-effect modeling was applied for Meta-analysis (STATA-17).Results: Out of the 159 documents retrieved, seven articles were deemed relevant after screening. An analysis involving 83 KC patients and 3,186 controls indicated that KC participants had significantly higher depression scores (SMD: 0.71 [0.31, 1.11]; p<0.01, I²: 52.7%). However, a meta-analysis of four studies comparing depression rates in KC patients (n=23,838) to control groups (n=73,482) found no increased risk of depression among KC patients compared to controls (OR: 1.13 [0.66, 1.94]; p=0.65, I²: 95.35%). Conclusion: While KC patients exhibit significantly higher depression scores compared to controls, a meta-analysis indicates no increased overall risk of depression among KC patients. These findings highlight the complexity of the relationship between keratoconus and mental health, warranting further investigation.